Ocular immunology: an overview of immune mechanisms operating in the eye - Agorogiannis, Eleftherios (Henry Stewart Talks, 2024)
Ocular anatomy, Ocular immunity, Immune privilege, Uveitis, Gut microbiome and systemic immunity, Age related macular degeneration (AMD), Parainflammation